Community Leaders Bane to Multinational Corporations Corporate Social Responsibility Policy Implementation in Niger Delta Nigeria (Global Journal of Human-Social Science, 2019)
The study examined community leaders as bane to multinational corporate social responsibility policy implementation in Niger Delta, Nigeria. The research was guided by three research questions. The study is a qualitative research based on case study design. Population of the study is 100 respondents' which consist of 20 staffs of 2 multinational, 30 leaders of men Community Based Organisations (CBOs), 26 members of women community based organisations and 24 members of registered youth community based organisations which were purposively drawn from two states of Niger Delta, (Rivers and Bayelsa States). The sample size for the study was 80, comprising 50 staffs of the multinational corporations, 10 members of men CBOs, 10 members of women CBOs and 10 members of youth registered organisations drawn using snow ball sampling technique.
Keywords: community leaders; multinational corporation; corporate social responsibility